Extramuscular and Intramuscular Course of the Nerve Innervating the Abdominal Part of the Pectoralis Major Muscle: An Anatomical Study with Regard to Transaxillary Endoscopic Subpectoral Breast Augmentation. Issue 3 (23rd February 2022) - Pretterklieber, Bettina; Metka, Susanne; Klöppel, Markus; Pretterklieber, Michael L.
Abstract : Background: During transaxillary endoscopic subpectoral breast augmentation, the innervation of the abdominal part of the pectoralis major muscle can be injured. The question has been raised whether this could even be of value, as for a better result, the caudal fibers of the pectoralis major muscle have to be detached from their origin. The authors' aim was to identify the exact position and the intramuscular course and target of these nerve branches. Methods: Fifty pectoralis major muscles and their supplying nerve branches from 27 formalin-fixed anatomical specimens were studied using macroscopic dissection and anthropometry. Furthermore, eight muscles underwent the modified Sihler procedure to determine the intramuscular course and target of the supplying nerve branches. Results: The branches for the abdominal part of the pectoralis major muscle pierced the pectoralis minor muscle or coursed around its lower border 3.2 to 8.4 cm from the tip of the coracoid process. Within the muscle, at least one small nerve branch, innervating the abdominal part, ascended into the lowermost portion of the sternocostal head, and anastomosed with the lowest small branch of its supplying nerve branches. Conclusions: Because of the variable position of the nerve branches, they may often cross the operative field during transaxillary endoscopic breast augmentation. However, their interruption can be of value, because weakening of the lower part of the pectoralis major muscle is desired to keep the implant in place, and to avoid animation deformity.